PENYULUHAN MAKANAN SEIMBANG TERHADAP ASUPAN ZAT GIZI, STATUS GIZI DAN PRESTASI BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN NEGERI SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - Daniel Robert; Inggit Posangi (POLTEKKES KEMENKES MANADO, 2013)
Good nutritional status is one determinant of the quality of human resources (HR) .Qualified human resources are characterized by strong physical , mental strength,good health and a master of science and technology . Some of the indicators thatmeasure the quality of human resources is the high and low levels of economic ,health and education. This study aims to determine the effect of a balanced dietcounseling on nutrient intake, nutritional status and student achievement SMKSangkub Bolaang North Mongondow.This research is a quasi experimental ( quasi experiment ) with the design of the Preand Post -test one group design . The timing of the June to July 2013 . Number ofsamples 50 were determined by purposive sampling . Data processing with SPSSversion 18.0.Teknik data analysis using univariate analysis to determine differencesbetween variables using t-test and bivariate analyzes to determine the effect of thestudy variables using paired sample t - test .The results of the analysis sample paired t - test counseling effect on energy intake ofa balanced diet significant difference p = 0.009 is smaller than t p = 0.005. Whereasprotein intake is known p = 0.482 ,which means there is no effect on the intake of abalanced diet counseling protein ( p > 0.05 ). For IMT (Nutritional status ) are notknown to influence where p > 0.05 ( p = 0.174 ). Student achievement before andafter studies found a significant difference p = 0.000 is smaller than t p = 0.05 . Noconclusions on the effect of counseling balanced food energy intake , but had noeffect on protein intake, there was no effect on the nutritional status and no influenceon student learning prestasil SMK Sangkub Bolaang North Mongondow